Analysis of Non Constant Viscosity on Avertical Oscillating Cylinder with Mhd Effects - Palani, G.; Sarojini, A.; Dhanasekaran, R. (International Journal of Engineering and Technology, 2018)
A numerical analysis was carried out on convective flow past a vertical oscillating cylinder with non-constant viscosity under the influence of magnetic field effects. The governing equations related to the flow problem are unsteady, nonlinear coupled partial differential equations. The same was transformed into a dimensionless form and the final form of equations was solved numerically. The approximate values of velocity, temperature, skin friction and Nusselt number are obtained. The viscosity considered as a function of temperature.
Keywords: Magnetic field; Oscillating; Skin friction; Velocity; Viscosity.